Methodological characteristics of Peruvian clinical practice guidelines, 2018 – 2023: A scoping review - Ana Brañez-Condorena; Blanca Solis-Chimoy; Jhonatan R. Mejia; Lesly Chávez-Rimache; David R. Soriano-Moreno; Jose Ernesto Fernández-Chinguel; Alvaro Taype-Rondan (PLoS ONE, 2025)
Background Clinical practice guidelines (CPGs) must be developed through a rigorous and transparent methodology to ensure the appropriateness and reliability of their recommendations. In Peru, little is known regarding how CPGs adhere to established methodological standards. Objective To describe the methodological characteristics of CPGs developed and published in Peru between 2018 and 2023. Methods We conducted a scoping review and searched CPGs on Google, Google Scholar, and relevant local organizational websites. To be included, CPGs had to self-identify as such, have full-text versions available online, provide explicit methodological descriptions, and base their recommendations on systematic reviews, with publication dates between January 2018 and December 2023. We presented the results descriptively and analyzed the methodological differences among CPGs from different organizations using Fisher’s exact tests. Results Out of 312 records assessed, 88 CPGs met the inclusion criteria. We found a declining publication trend over the study period: 39 CPGs were published in 2018–2019, 30 in 2020–2021, and 19 in 2022–2023. Most CPGs (60.2%) were developed by the Peruvian Social Security Health Insurance (EsSalud). Oncology was the most prevalent specialty of the CPGs (20.5%) and most CPGs (96.6%) included disease management. 23.7% of CPGs used ≥ 3 search engines, and 76.3% showed the risk of bias assessment. Although most CPGs indicated using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) methodology (94.3%), 30.7% missed Summary of Findings tables, 38.6% did not include Evidence-to-Decision frameworks, and only 5.7% used minimal important difference for at least one question. Additionally, economic analyses were infrequently sought or included. Conclusions This study highlights significant methodological deficiencies in Peruvian CPGs, including inadequate reporting of search strategies, bias assessments, and key GRADE components. Addressing these shortcomings is crucial for enhancing the quality and reliability of CPGs and promoting equitable healthcare delivery in Peru.